Determining the resolution of a tracer for magnetic particle imaging by means of magnetic particle spectroscopy - Remmo, Amani; Wiekhorst, Frank; Kosch, Olaf; Lyer, Stefan; Unterweger, Harald; Kratz, Harald; Löwa, Norbert (RSC Advances, 2023)
Magnetic particle imaging (MPI) is an imaging modality to quantitatively determine the three-dimensional distribution of magnetic nanoparticles (MNPs) administered as a tracer into a biological system. Magnetic particle spectroscopy (MPS) is the zero-dimensional MPI counterpart without spatial coding but with much higher sensitivity. Generally, MPS is employed to qualitatively evaluate the MPI capability of tracer systems from the measured specific harmonic spectra. Here, we investigated the correlation of three characteristic MPS parameters with the achievable MPI resolution from a recently introduced procedure based on a two-voxel-analysis of data taken from the system function acquisition that is mandatory in Lissajous scanning MPI. We evaluated nine different tracer systems and determined their MPI capability and resolution from MPS measurements and compared the results with MPI phantom measurements.
CRIS-Team Scopus Importer:2023-07-07